2009
DOI: 10.1080/10673220902996734
|View full text |Cite
|
Sign up to set email alerts
|

The Hypothalamic-Pituitary-Adrenal Axis in Borderline Personality Disorder

Abstract: comorbid diagnoses and clinical features such as trauma history and symptom severity may have variable, interacting influences on the psychoneuroendocrine profile in BPD. Also explored here are the implications of these findings for developing possible models of HPA-axis dysfunction in BPD, for identifying potential targets for treatment, and for improving the methodology of future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 106 publications
0
46
0
4
Order By: Relevance
“…57 A specific vulnerability to stress (higher emotional intensity in response to stressors and a delayed return to baseline affect) has been proposed for individuals with BPD, 58 which might be associated with the hypothalamic-pituitary-adrenal axis (HPAA). 59 Adults with BPD show an attenuated cortisol response to acute stress, 60 and this has also been found in adolescents engaging in repetitive NSSI. 61 More numerous self-harm behaviors in adolescents with BPD were associated with increased pituitary volumes, 62 suggesting greater basal activation of the HPAA.…”
Section: Neurobiological Findingsmentioning
confidence: 99%
“…57 A specific vulnerability to stress (higher emotional intensity in response to stressors and a delayed return to baseline affect) has been proposed for individuals with BPD, 58 which might be associated with the hypothalamic-pituitary-adrenal axis (HPAA). 59 Adults with BPD show an attenuated cortisol response to acute stress, 60 and this has also been found in adolescents engaging in repetitive NSSI. 61 More numerous self-harm behaviors in adolescents with BPD were associated with increased pituitary volumes, 62 suggesting greater basal activation of the HPAA.…”
Section: Neurobiological Findingsmentioning
confidence: 99%
“…studies of BPD are rather mixed (for example, see the review by Zimmerman and Choi-Kain 8 ). Comorbid disorders, such as posttraumatic stress disorder (PTSD) and major depressive disorder (MDD), which are frequent among patients with BPD and affect HPA axis functioning, as well as other confounding variables, such as sex, menstrual cycle and age, may at least partly explain these inconsistencies.…”
mentioning
confidence: 99%
“…Comorbid disorders, such as posttraumatic stress disorder (PTSD) and major depressive disorder (MDD), which are frequent among patients with BPD and affect HPA axis functioning, as well as other confounding variables, such as sex, menstrual cycle and age, may at least partly explain these inconsistencies. 8 The cause of HPA axis dysregulations is thought to result from adverse experiences in early life, with traumatic childhood experiences and sexual abuse in childhood impairing neurobiological systems involved in the stress response. 9,10 In addition to disturbances in HPA axis functioning, brain imaging studies have revealed volumetric alterations in structures crucially involved in the regulation of stress responses in patients with BPD.…”
mentioning
confidence: 99%
“…Rappelons que la réponse physiologique immédiate à un stress provoque une activation de l'axe hypothalamo-pituitairo-hypophysaire qui entraîne une cascade d'effets sur l'activité de la noradrénaline, du cortisol, de la glande thyroïde et du système des opioïdes (Simeon et al, 2007 ;Zimmerman et Choi-Kain, 2009 ;Wingenfeld et al, 2010).…”
Section: Constatations Neurophysiologiques Sur La Dissociationunclassified
“…Selon les analyses statistiques, la suppression du cortisol semble plus reliée au TSPT qu'au TP (Shea, 1999 ;Lewis et Grenyer, 2009). Les données sont de ce fait difficiles à interpréter lorsqu'il s'agit de faire la part des choses entre l'influence du traumatisme ou d'une personnalité limite sur la réponse physiologique au stress (Flory et al, 2009 ;Zimmerman et Choi-Kain, 2009 Toujours dans le champ de recherche en neuro-imagerie, les sujets avec TPL ou TPST ont aussi des volumes réduits des noyaux de l'hippocampe et de l'amygdale en comparaison à des sujets normaux (Lewis et Grenyer, 2009 ;Wingenfeld et al, 2010). Par contre, Donegan et al (2003) ont trouvé une amygdale gauche plus activée chez des sujets avec TPL en comparaison à des sujets normaux en imagerie fonctionnelle.…”
Section: Constatations Neurophysiologiques Sur La Dissociationunclassified